Septum resection versus expectant management in women with a septate uterus: an international multicentre open-label randomized controlled trial. Issue 5 (1st April 2021) - Rikken, J F W; Kowalik, C R; Emanuel, M H; Bongers, M Y; Spinder, T; Jansen, F W; Mulders, A G M G J; Padmehr, R; Clark, T J; van Vliet, H A; Stephenson, M D; van der Veen, F; et al.
Abstract: STUDY QUESTION: Does septum resection improve reproductive outcomes in women with a septate uterus? SUMMARY ANSWER: Hysteroscopic septum resection does not improve reproductive outcomes in women with a septate uterus. WHAT IS KNOWN ALREADY: A septate uterus is a congenital uterine anomaly. Women with a septate uterus are at increased risk of subfertility, pregnancy loss and preterm birth. Hysteroscopic resection of a septum may improve the chance of a live birth in affected women, but this has never been evaluated in randomized clinical trials. We assessed whether septum resection improves reproductive outcomes in women with a septate uterus, wanting to become pregnant. STUDY DESIGN, SIZE, DURATION: We performed an international, multicentre, open-label, randomized controlled trial in 10 centres in The Netherlands, UK, USA and Iran between October 2010 and September 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women with a septate uterus and a history of subfertility, pregnancy loss or preterm birth were randomly allocated to septum resection or expectant management. The primary outcome was conception leading to live birth within 12 months after randomization, defined as the birth of a living foetus beyond 24 weeks of gestational age. We analysed the data on an intention-to-treat basis and calculated relative risks with 95% CI. MAIN RESULTS AND THE ROLE OF CHANCE: We randomly assigned 80 women with a septate uterus to septum resection (n = 40) or expectant management (n = 40). We excluded one woman who underwent septum resection from the intention-to-treat analysis, because she withdrew informed consent for the study shortly after randomization. Live birth occurred in 12 of 39 women allocated to septum resection (31%) and in 14 of 40 women allocated to expectant management (35%) (relative risk (RR) 0.88 (95% CI 0.47 to 1.65)). There was one uterine perforation which occurred during surgery (1/39 = 2.6%). LIMITATIONS, REASONS FOR CAUTION: Although this was a major international trial, the sample size was still limited and recruitment took a long period. Since surgical techniques did not fundamentally change over time, we consider the latter of limited clinical significance. WIDER IMPLICATIONS OF THE FINDINGS: The trial generated high-level evidence in addition to evidence from a recently published large cohort study. Both studies unequivocally do not reveal any improvements in reproductive outcomes, thereby questioning any rationale behind surgery. STUDY FUNDING/COMPETING INTEREST(S): There was no study funding. M.H.E. reports a patent on a surgical endoscopic cutting device and process for the removal of tissue from a body cavity licensed to Medtronic, outside the scope of the submitted work. H.A.v.V. reports personal fees from Medtronic, outside the submitted work. B.W.J.M. reports grants from NHMRC, personal fees from ObsEva, personal fees from Merck Merck KGaA, personal fees from Guerbet, personal fees from iGenomix, outside the submitted work. M.G. reports several research and educational grants from Guerbet, Merck and Ferring (location VUMC) outside the scope of the submitted work. The remaining authors have nothing to declare. TRIAL REGISTRATION NUMBER: Dutch trial registry: NTR 1676 TRIAL REGISTRATION DATE: 18 February 2009 DATE OF FIRST PATIENT'S ENROLMENT: 20 October 2010